Autocratic Challenges to International Human Rights Law: A Chinese Case Study - Pils, Eva (Current Legal Problems, 2022)
Drawing on a case study of the implications of China's atrocities in Xinjiang in the context of China's historical engagement with UN and its human rights mechanisms, this article examines autocracies' impact on the institutions and practices of international human rights law. It argues that that rather than creating new law that turns international law as a whole (more) authoritarian, the Chinese party-state is primarily - and even more dangerously - corroding its institutions and practices, while expanding neo-totalitarian governance discourses and practices to the global level. The autocratic corrosion of international human rights law institutions is exacerbated by attempts to weaken accountability under international human rights law from within liberal democracies, amounting to synergic corrosive effects. Yet, the corrosion of practices norms and institutions must not be equated with the elimination of human rights as powerful ideas underpinning responses to the institutional challenges identified here.
CRIS-Team Scopus Importer:2024-06-26
Keywords: autocracy; China; human rights; international rule of law

Charter 08 and violent resistance: The dark side of the Chinese Weiquan movement - Pils, Eva (Hong Kong University Press, HKU, 2012)
If, fantastically, an opinion poll on "Do you support Charter 08?" could be conducted in China today, its results would have to be read bearing in mind that you cannot look up "Charter 08" on the domestic Internet, and that any expression of support for it may result in state persecution. Attempts to measure the impact of or support for the Charter would therefore be inherently limited,1 even though naturally, we will continue to ask ourselves how strong such support is.2 Charter 08's significance lies not in its measurable impact or support but in its proposition of a peaceful kind of political change, a proposition that represents but one group within an increasingly diverse opposition to the current government. Charter 08 supporters face not only government repression, but also opposition from those who do not approve of its supporters' apparent advocacy of non-violence. This chapter seeks to understand the perspective of those represented by the Charter, as well as some of the perspectives of those within the wider Chinese rights defense movement who do not consider themselves represented by it. It draws on a distinction often used by rights defenders themselves, namely that between "grassroots" and "elite" rights defense or weiquan; but also urges recognition of the fact that an analysis of attitudes, ideals and social practices among rights defenders shows these groups to be mingling and interacting, rather than rigidly separate. 3 It is argued here that the Charter attempts to pose an enlightened alternative to the popular political opposition's and weiquan movement's darker sides, because its agenda is non-violent and non-vindictive. Its proposals are premised on values germane to a practice of adequate rights protection, but increasingly at risk of being sacrificed to public anger and destructiveness in China's volatile society, in which "rights defense" is not infrequently combined with support for strategies and policies inimical to the very idea of rights. Like the distinction between "grassroots" and "elite," so too is the imagery of light and shadow used here complex and unstable - for the "darkness" attributed to parts of the "grassroots" movement contrasts starkly with the light, warmth, and transparency people in this movement apparently desire: "Sunshine Charity" (Yangguang Gongyi), as the name of one of those "grassroots" groups may serve as a good illustration. The darkness in which much of weiquan is situated, on the other hand, is in many ways due to especially vicious state repression, and also affects "professional" or "elite" weiquan, in particular human rights lawyers. In the following pages, I first explain the stagnation of constitutional change (or reform) as a result of the inherent contradictions within the current constitutional setup, the weiquan movement's early successes, and its current repression. Then I turn to examining attitudes of heightened enmity and vindictiveness among the grassroots weiquan movement. These can be understood as a consequence of repression, yet they also complement and enable some government practices of repression. Lastly I discuss how public figures in the weiquan movement, including some of the Charter's prominent signatories, view Chinese society's prospects for change, focusing not on views about the end goal, captured in the Charter itself, but on views about the way to get there. © Hong Kong University Press 2012. All rights reserved.
CRIS-Team Scopus Importer:2024-06-26

China, the Rule of Law, and the Question of Obedience: A Comment on Professor Peerenboom - Pils, Eva (Hague Journal on the Rule of Law, 2015)
Commenting on Randall Peerenboom’s analysis of an October 2014 decision by China’s ruling Communist Party on legal reform, I make two points here. First, I argue that Peerenboom’s in my view inaccurate account of (positivistic and naturalist) liberal conceptions of law prevents him from understanding the implications of this decision’s deeply illiberal commitment to power concentration and Party supremacy over law. This account fails to appreciate the resources which liberalism offers to engage critically with the operation of a legal system such as that of China, where – as I point out drawing on my work on human rights lawyers – repression of legal and political rights advocacy have been worsening. Second, I suggest that both the Decision and Peerenboom’s analysis do not fully take into account the nature and scope of the challenges the Party-State is facing, especially the challenge arising from an increasing momentum for civic activism and civil disobedience.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Authoritarianism; China; Human rights; Liberalism; Repression; Rule of law

Comments on the 2012 revision of the Chinese criminal procedure law - Rosenzweig, Joshua D.; Sapio, Flora; Jue, Jiang; Biao, Teng; Pils, Eva (Edward Elgar Publishing Ltd., 2013)
CRIS-Team Scopus Importer:2023-03-21

Comparative perspectives on criminal justice in China - McConville, Mike; Pils, Eva (Edward Elgar Publishing Ltd., 2013)
'This highly informative and engaging volume on the Chinese criminal justice system today provides a window into the vagaries of law and its operation in the People's Republic. McConville and Pils bring together an impressive array of scholars whose studies span the criminal process. From initial police investigation, through to prosecution and sentencing of defendants, we see how dominant values in the Chinese state and its structures of power make the practice of criminal justice today still intensely political.' - Susan Trevaskes, Griffith University, Australia. © The Editors and Contributors Severally 2013. All rights reserved.
CRIS-Team Scopus Importer:2023-03-21

Contending conceptions of ownership in urbanizing China - Pils, Eva (Cambridge University Press, 2010)
Among the incidents drawing attention to the problem discussed here, the self-immolation of a woman named Tang Fuzhen in December 2009 was one of the most widely discussed. Facing the forced demolition of her home, she stood on the roof of the building, doused herself in petrol and, after vainly urging the demolition team to stop beating members of her family, set herself on fire. Her suicide (she succumbed to her injuries a few days later) was captured on camera, and the video clip showing her, a dark, then suddenly aflame, silhouette against the sky, amongst the shouts of shocked observers in the street below, was widely circulated on the internet. As urbanisation has progressed rapidly, the effects of urban development – to be precise, of urban redevelopment and of the expansion of cities into the countryside – on citizens affected by demolition and expropriation of land or houses has been great in China. While they have no real choice in the face of an order to ‘develop’ or redevelop their area through urban construction, not all residents actually oppose such measures. Some are glad to accept compensation payments, which can be substantial and that have given rise to the term ‘demolition nabob’. But invariably, some residents are opposed to their removal, and become involved in fights with the government that may cost them far more than just their residences. The experiences of these activist evictees have drawn much public attention, and are among the reasons for continued criticism of the existing regime of ownership and use rights in immoveable property (land and buildings).
CRIS-Team Scopus Importer:2024-06-26

Die Debatte über Deutschlands Umgang mit China: Versuch einer Einordnung - Pils, Eva; Weber, Ralph (Leviathan, 2024)
Germany has been discussing its relation to the People’s Republic of China and its party rule for a while. Based on the German government’s China strategy, we ask for a framework of analysis and evaluation. We criticize the failure to recognize transnational realities, demand a much clearer foregrounding of normative tensions and emphasize the duties limiting state actors’ strategic options for action in a liberal democracy.
CRIS-Team Scopus Importer:2024-10-18
Keywords: autocracy; China; human rights; openness; resilience; transnationality

'Disappearing' China's human rights lawyers - Pils, Eva (Edward Elgar Publishing Ltd., 2013)
CRIS-Team Scopus Importer:2023-03-21

Introduction: Discussing "Civil society" and "Liberal communities" in China - Pils, Eva (China Perspectives, 2012)
CRIS-Team Scopus Importer:2024-06-26

Liu Xiaobo, charter 08 and the challenges of political reform in China - Béja, Jean Philippe; Fu, Hualing; Pils, Eva (Hong Kong University Press, HKU, 2012)
In December 2008 some 350 Chinese intellectuals published a manifesto calling for reform of the Chinese constitution and an end to one-party rule. Known as "Charter 08", the manifesto has since been signed by more than 10,000 people. One of its authors, Liu Xiaobo, was awarded the Nobel Peace Prize in 2010 but has remained in prison since 2009 for subversive crimes. This collection - the first of its kind in English - examines the trial of Liu Xiaobo, the significance and impact of Charter 08, and the prospects for reform in China. The collection includes contributions from legal and political experts from around the world, a detailed account of Liu's trial by his defence lawyers, and a passionate - and ultimately optimistic - account of resistance, repression and political change by the human rights lawyer Teng Biao. © Hong Kong University Press 2012. All rights reserved.
CRIS-Team Scopus Importer:2024-06-26

Peasants' struggle for land in China - Pils, Eva (Routledge Taylor & Francis Group, 2009)
CRIS-Team Scopus Importer:2024-06-26

The Party’s Turn to Public Repression: An Analysis of the ‘709’ Crackdown on Human Rights Lawyers in China - Pils, Eva (China Law and Society Review, 2018)
The intensified and more public repression of civil society in China is part of a global shift toward deepened and technologically smarter dictatorship. This article uses the example of the ‘709’ government campaign against Chinese human rights lawyers to discuss this shift. It argues that the Party-State adopted more public and sophisticated forms of repression in reaction to smarter forms and techniques of human rights advocacy. In contrast to liberal legal advocacy, however, the Party-State’s authoritarian (or neo-totalitarian) propaganda is not bounded by rational argument. It can more fully exploit the potential of the political emotions it creates. Along with other forms of public repression, the crackdown indicates a rise of anti-liberal and anti-rationalist conceptions of law and governance and a return to the romanticisation of power.
CRIS-Team Scopus Importer:2024-06-26
Keywords: authoritarianism; China; human rights advocacy; political emotion; repression; resistance; totalitarianism

The practice of law as conscientious resistance: Chinese weiquan lawyers' experience - Pils, Eva (Taylor and Francis, 2010)
CRIS-Team Scopus Importer:2024-06-26